Effects of Origanum majorana essential oil and antibiotics on the quality of frozen thawed Beni Arouss buck semen. Issue 2 (28th October 2022) - Kchikich, Amr; Kirschvink, Nathalie; El Kadili, Sara; Raes, Marianne; El Otmani, Samira; Chebli, Youssef; Bister, Jean‐Loup; El Amiri, Bouchra; Barrijal, Said; Chentouf, Mouad
Abstract: This study aims to investigate the effects of Origanum majorana (OM) essential oil (EO) at different concentrations and antibiotics on post‐thawed Beni Arouss buck semen quality. Semen collection was performed using artificial vagina from eight Beni Arouss bucks. Ejaculates were pooled, divided into 12 equal aliquots, washed and diluted to 400 × 10 6 sperm/ml (with 7% of glycerol). Skim milk–based extender was supplemented with different concentrations of OM EO (0%; 0.01%; 0.02%; 0.03%; 0.04% and 0.05%) without antibiotics, marked as (CTR−), (M1−), (M2−), (M3−), (M4−) and (M5−), and with 50 mg of streptomycin and 50, 000 IU of penicillin per 100 ml, marked as (CTR+), (M1+), (M2+), (M3+), (M4+) and (M5+), respectively. Aliquots were cooled to 4°C, then frozen in 0.25 ml straws with a programmable freezer and finally stored in liquid nitrogen for 48 h. Thawing was performed at 37°C for 30 s. Motility, live sperm, sperm abnormalities, membrane integrity, lipid peroxidation and bacterial growth were evaluated after thawing. Among the tested extenders, M2+ improved all semen quality parameters. Sperm motility, live sperm and membrane integrity increased significantly, while the number of abnormal sperm and bacterial growth decreased significantly. The toxic effect of OM EO, with and without antibiotics, appeared beyond 0.03%. In conclusion, M2+ is recommended to improve the cryopreservation of Beni Arouss buck semen.